Sustainable Interior Design of The Living Room in a Muslim Residence: Concept and Implementation: - - Nurjayanti, Widyastuti; Karban, Abdullah Saeed (Sinektika: Jurnal Arsitektur, 2025)
The interior design of the living room in a Muslim residence needs attention, because privacy in the house is strictly maintained, so it is necessary to implement a living room interior design that is based on Sharia. The objectives of this research are 1). Developing a living room interior design concept, 2) implementing an Islamic home interior design that is functional, aesthetic, and Islamic. This design is a combination of Islamic and sustainable concepts. The Sharia referred to is the mahram structure of the Muslim family, which has an impact on the hierarchy of spatial zones. The supporting approach is Islamic ethics in space and Islamic decorative arts. Sustainability is realized in the choice of environmentally friendly materials. The method used is a mixed literature study that takes references to Islamic values ​​mentioned in the Al-Qur'an and Hadith and then applies them to research related to the concept of sustainable housing. The results of this research are the concept and implementation of sustainable living room interior design, including the hijab, Islamic decorative arts, sustainable architecture, and environmentally friendly materials.